Supreme Court agenda setting strategic behavior during case selection - Sommer, Udi.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Much research is devoted to the decision-making power and precedent set by the Supreme Court. Less attention, however, is given to the strategic behavior during case selection. This book argues that case selection is done strategically, and by means of various criteria - influencing its constitutional position and importance.
Keywords: Science; Science; Science, general